Defects, faults and accidents of contemporary constructions - Kraus Michal; Vondráčková Terezie; Nývlt Vladimír (MATEC Web of Conferences, 2017)
The paper deals with the defects, faults and accidents of contemporary constructions. The increasing number of constructions provides higher probability of occurrence of the defects. The defect is a lack of structure, which is caused by faulty design, inadequate or imperfect execution. The defect may affect the performance of the structure. The fault is the temporary or permanent loss of ability to perform its function. A defect may be causing disorder of structure. A special attention is paid to the defects and disruptions of buildings, which caused death or serious injuries (human or animal), safety hazards or major property damage. The aim of the paper is a description and analysis of data from the Construction and Technical Prevention System (CTPS) in the Czech Republic in several last years. It is necessary to take measures to prevent serious or excessively repetitive defects of buildings.